Evaluation of bacteriological profile and antibiotic sensitivity patterns in children with urinary tract infection: A prospective study from a tertiary care center - Ranjana Badhan; Dig Vijay Singh; Lashkari R Badhan; Anureet Kaur (Indian Journal of Urology, 2016)
Introduction: Development of regional surveillance programs is necessary for the development of community-acquired urinary tract infection (UTI) guidelines, especially for sub-urban and rural areas where empirical treatment is the mainstay in the absence of proper diagnostic modalities. Our aim was to evaluate the bacteriological profile and antibiotic sensitivity patterns in children with UTI prospectively from a tertiary care center. Methods: A total of 800 children up to 18 years of age with suspected UTI attending our center were included. For all suspected cases urine microscopy, gram staining, and culture were done. Antibiotic sensitivity was performed on selected antimicrobials using disk diffusion method following Clinical Laboratory Standards Institute guidelines. Results: Majority of pathogens were isolated from female (54.2%) patients. Pre-teens (52.1%) and teens (27.1%) were most commonly affected age group. The most common presentation in culture-proven UTI was fever with urinary symptoms (33.3%). In a group of 192 patients 26.7% had proven UTI. Escherichia coli (42.3%) was the most common aetiological agent, followed by Enterococcus fecalis (13.5%), Klebsiella spp. (11.5%) and Staphylococcus aureus (11.5%). Most active antibiotics against Gram-negative isolates were nitrofurantoin, cefotaxime, and amikacin. Gram-positive isolates were sensitive to nitrofurantoin, cotrimoxazole, and novobiocin. Conclusion: E. coli was the commonest isolate. The organisms grown in significant numbers were E. fecalis, Klebsiella spp. and S. aureus, causing UTI in 0–18 years of age group. Gram-negative isolates were sensitive to nitrofurantoin, amikacin, and cefotaxime. Gram-positive isolates were sensitive to nitrofurantoin, cotrimoxazole, and novobiocin. Prospective, regional studies are ensured periodically to explain bacteriological profile and antibiotic sensitivity patterns to be applicable for children with UTI over that geographic area.